O.I.C.-based design of mono-symmetric I-sections under simple load cases. (May 2022) - Li, Liya; Gérard, Lucile; Langlois, Sébastien; Boissonnade, Nicolas
Abstract: This paper studies the ultimate resistance of mono-symmetric hot-rolled and welded sections under axial compression, major-axis bending or minor-axis bending as affected by local buckling and material yielding. Following the development of advanced non-linear shell finite element models and their validation against existing test data, extensive non-linear numerical analyses are carried out. Various parameters including two manufacturing types, three steel grades and various section dimensions are considered, to investigate the influence of mono-symmetric levels with various flange widths ratios b 1 / b 2 on section behaviour. The numerical results are then used to assess a proposed extension of the Overall Interaction Concept (O.I.C.) to mono-symmetric I-shaped sections. Systematic comparisons with existing standards – Eurocode 3 and the American Standards – and the proposed O.I.C.-based method prove the new approach to be more consistent, accurate and straightforward.